Main reasons for ukrainian students labor migration - Komarova, K. O. (ТДАТУ, 2019)
According to statistics, nearly half of the emigrants are young people aged 19-25. In Ukraine, student employment programs have been around for 20 years. Every year, thousands of students go to conquer the world, some return for personal reasons, but nearly 80% remain to work on.
Keywords: migration population growth; migration; labor migration dynamics